2016
DOI: 10.5815/ijeme.2016.06.04
|View full text |Cite
|
Sign up to set email alerts
|

Opinion Mining of Online Product Reviews from Traditional LDA Topic Clusters using Feature Ontology Tree and Sentiwordnet

Abstract: Online product reviews provide data about the user"s perspective on the features that were experienced by them. Product features and corresponding opinions form a major part in analyzing the online product reviews. Extracting features from a huge number of reviews is classified into three major categories such as utilizing language rules, sequence labeling as well as the topic modeling. Latent Dirichlet Allocation (LDA) is one such topic model which clusters the document words into unsupervised learned topics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…A comparison regarding main approaches [4,13,28,37,45,46,51] with respect to our proposed criteria is shown in Table 1 and illustrates that all existing studies use a semiautomatic approach to learn domain-specific ontologies and use several criteria to evaluate ontologies. Also, the inconsistency regarding entries is still an open challenge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison regarding main approaches [4,13,28,37,45,46,51] with respect to our proposed criteria is shown in Table 1 and illustrates that all existing studies use a semiautomatic approach to learn domain-specific ontologies and use several criteria to evaluate ontologies. Also, the inconsistency regarding entries is still an open challenge.…”
Section: Discussionmentioning
confidence: 99%
“…We observe that, in the extraction phase, all existing systems rely only on simple terms and do not extract complex ones leading consequently to produce syntactic inconsistency. In the classification phase, we also note that [13,46] and Posch [45] use a certain document representation method which does not consider semantic relations among different words. Gutiérrez-Batista et al [28], Asfari et al [4], and Zavitsanos et al [51] use the probabilistic document representation to recognize terms of documents and to use topic probability distribution for representations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [18], proposed a method for topic identification in web documents using web design features. In [19], opinion mining performed on online product reviews with LDA topic clusters using feature ontology tree and sentiwordnet. Also, in [20] Mann-Kendall test is used to understand the nature of trends in rainfall of different regions in India.…”
Section: Related Workmentioning
confidence: 99%
“…Htay and Lynn [8] proposed a method to extract opinion words or phrases for each feature by attaining the patterns from the review text through some specific parts of speech (POS) in order to generate summarized information that helps customers make a better selection. Santosh, Babu, Prasad, and Vivekananda [9] reported that, by applying the topic model, we can construct a domain-independent Feature Ontology Tree (FOT) in order to identify the characteristics of products. Although most of these methods focused on whether the review is positive or negative, or the main topic of the review, the impressions related to affective evaluation are not yet specifically reated.…”
Section: Introductionmentioning
confidence: 99%